Identity strategies, cultural practices and citizenship recovery: mauritanian refugees in the Senegal Valley - Kane, Mamadou Seydou (2013)
In 1989 a conflict arose on the Senegal-Mauritania border, resulting in violence by populations on either side against those suspected of “foreign” origins. This situation entailed mass slaughters of people of Senegalese descent in Mauritania and expulsion for the luckier ones. Their assimilation in the Senegalese part of the borderland has been made partly easier by the language they share with the host communities, which enabled them, on arrival, to undertake activities that would also ensure their integration. Mauritanian refugees now have the possibility to move freely between their former sites and their new environment. Yet this process of losing and regaining their status is paralleled by a more complex process of identity seeking or recovery. This paper examines these identity issues by focusing on the experience of the Djolly Senegal refugee community, and also on the cultural bridging strategies that they have developed, with a particular interest in representations and discourse.